Financial Literacy for Youth at Vocational School of Accounting Department of Pab 8 Sampali Percut Sei Tuan District, Serdang Regency, North Sumatera - Bayu Wulandari; Herlin Munthe; Maya Sabirina Penggabean; Jessi Charina Sembiring; Thomas Firdaus Hutahaean; Ribka Sari Butar-Butar (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Community service activities at SMK PAB 8 Sampali, Percut Seituan District, district. Deli Serdang North Sumatra aims to increase the understanding of financial literacy in students of SMK PAB 8 Sampali. This is done because financial literacy is very high important to understand and apply in life, be one of the six basic literacy. The goal is that every student of SMK PAB 8 Sampali, Percut Seituan District, Kab. Deli Serdang North Sumatra has an understanding of financial literacy that can be used not only now, but even after they work in the household. The method used is socialization by providing motivation with lectures and discussions in the form of question and answer sessions. The results revealed that financial literacy is still a new knowledge for some students. Even though financial literacy is very influential positive financial behavior and financial management itself. By following This activity, they hope will be able to increase financial literacy, and impact on good financial management and avoid various crimes finance. In this case conducting presentations with various themes related to finance including (1). understanding of basic financial reporting concepts, (2) excellent service in the banking world, (3). saving in generation Z, (4). the importance of investing at a young age, (5). digital capital market financial investment, (6) investment (mutual funds). In the implementation carried out / students enthusiastically in the process of implementing students and at the end with a question and answer process.